An evaluation on the dispensing of medicines (floorstocks) in Emergency Department and Pharmacy Department of Hospital Seberang Jaya, Pulau Pinang - Wan Faizal Maizahani, Wan Intan Fatiha; Mohd Nizar, Muhammad Syahmi; Aliah, Fatimah (2013)
Objective: To study the dispensing practices and the management of drugs (floor stocks) by other healthcare practitioners at emergency department of Hospital Seberang Jaya.